Manajemen Pesantrenpreneur untuk Mewujudkan Kemandirian Ekonomi Pesantren: Studi Kasus Pondok Pesantren Modern Al-Kautsar Sumbersari, Srono, Banyuwangi - Kholilia, Zulfa; Khamidi, Amrozi; Hazin, Mufarrihul; Suyanto, Ahmad (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2026)
Islamic boarding schools (Pesantren) play a strategic role not only as educational and da'wah institutions, but also as institutions for the economic empowerment of the community. Law Number 18 of 2019 concerning Islamic Boarding Schools (Pesantren) emphasizes the role of Islamic boarding schools in education, da'wah, and community empowerment, including economic empowerment. This article aims to analyze the management of Islamic boarding school entrepreneurs in realizing economic independence in Islamic boarding schools, using a case study of the Al-Kautsar Modern Islamic Boarding School in Sumbersari, Srono, Banyuwangi. This research uses a qualitative approach with a case study design, focusing the analysis on the management functions of planning, organizing, implementing, and controlling (POAC). The study results indicate that Al-Kautsar Modern Islamic Boarding School has developed a pesantren business unit as an alternative source of income. However, the implementation of pesantrenpreneur management still requires strengthening the planning system, organizational structure, implementation mechanisms, and integrated evaluation and control. Systematically strengthening pesantrenpreneur management has the potential to promote economic independence in Islamic boarding schools while strengthening institutional commitment without abandoning Islamic educational values.